Cyber-physical-system for representing a robot end effector - Müller, Fabian; Deuerlein, Christian; Koch, Michael (Procedia CIRP, 2021)
Programming by Demonstration (PbD) is a method to program robots through the performance of a task by humans. Most implementations are online methods that use visual or force feedback of the demonstrator. However, we developed an offline programming approach for PbD with a special input device within an Augmented Reality Environment. Therefore, this paper aims to answer how the characteristics and functionality of the end effector of a jointed-arm robot can be represented by a haptic input device in order to perform PbD. The PbD process is first carried out on a digital twin of the robot, visualized to the user in real physical space by means of augmented reality technology. The programming of the digital twin can later be transferred to the real robot. The haptic input device in this context is the main part of the Cyber-Physical-System (CPS), which enables the user to interact with the virtual robot. Therefore, the specification of the mechanical and software components of the CPS is of main importance. Within this paper, strategies for the implementation of shape and function abstraction, as well as for ensuring communication, have been worked out. The physical shape of the CPS is kept generic and is only subject to ergonomic restrictions. However, Augmented Reality overlays the physical shape with an exact digital image of the end effector used later in the process. Nevertheless, the physical characteristics of the real robot should be represented as real as possible by the CPS. Therefore, the CPS is equipped with various sensors and actuators. With the CPS it is possible to determine contact forces and to manipulate objects to a certain extent in order to teach gripping strategies to the digital twin. An operating system was developed for communication and control of the electronic components. For the validation of the functionality of the CPS an exemplary PbD process was developed, the results were analyzed and evaluated.